(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The political leadership in the country was in the hands of the Bolsheviks. They were, in a sense, given the difficult political situation in the country, temporarily allowing local nations to act around the mission, which in turn was nothing but tactical cunning. Nevertheless, members of the party who grew up among the local ethnic groups united around the office and fought for the rights of the indigenous people as well.